2004
DOI: 10.1002/jcu.10232
|View full text |Cite
|
Sign up to set email alerts
|

Experience with focused abdominal sonography for trauma (FAST) in 313 pediatric patients

Abstract: FAST is an effective tool in screening pediatric trauma patients for blunt abdominal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…Over 60% of all pediatric trauma deaths are due to motor vehicle injuries alone, resulting in a greater loss of life in children than cancer, heart disease, respiratory conditions, and infections combined. It is estimated that 10% of deaths are due to abdominal injuries [2].…”
Section: Introductionmentioning
confidence: 99%
“…Over 60% of all pediatric trauma deaths are due to motor vehicle injuries alone, resulting in a greater loss of life in children than cancer, heart disease, respiratory conditions, and infections combined. It is estimated that 10% of deaths are due to abdominal injuries [2].…”
Section: Introductionmentioning
confidence: 99%
“…Focused abdominal ultrasound for trauma (FAST) enables the detection of free intraperitoneal fluid (ie, blood) and the identification of intraabdominal injuries in adults with a high sensitivity of 63% to 99% [16][17][18][19]. A few reports have shown that FAST has been used in children to detect free intraperitoneal fluid with a sensitivity of 56% to 93% and a specificity of 79% to 97% [20][21][22][23].…”
mentioning
confidence: 98%
“…Besides thorough clinical investigation, ultrasound has been successfully applied as a diagnostic tool in adults and children with blunt abdominal trauma [16][17][18][19][20][21][22][23]. Focused abdominal ultrasound for trauma (FAST) enables the detection of free intraperitoneal fluid (ie, blood) and the identification of intraabdominal injuries in adults with a high sensitivity of 63% to 99% [16][17][18][19].…”
mentioning
confidence: 99%
“…L'esame clinico nella diagnosi precoce di emoperitoneo nel trauma addominale chiuso presenta una sensibilità compresa tra il 39 ed il 70%, in cambio tuttavia di una buona specificità (90%) 17,46 . L'ecografia mirata alla ricerca di emoperitoneo post-traumatico in uno studio condotto su un'ampia popolazione pediatrica dimostra invece una sensibilità del 92% ed una specificità del 97% 47 . Nell'adulto sono riportati analoghi valori di sensibilità nella ricerca di emoperitoneo, con variazioni dal 92% al 99% a seconda dell'esperienza dell'operatore e delle condizioni del paziente traumatizzato 48-50. Momento di esecuzione: il "point of care" L'esame EFAST, integrato nella gestione ABCDE del trauma, trova collocazione naturale alla fine della valutazione primaria (primary survey): E = Ex posure potrebbe acquisire o arricchirsi dell'accezione E = Echography.…”
Section: Evoluzione Della Fast: La Extended Fast (O Efast)unclassified